UM PANORAMA DOS ESTUDOS SOBRE CONTAMINAÇÃO POR MERCÚRIO NA AMAZÔNIA LEGAL NO PERÍODO DE 1990 A 2005 - AVANÇOS E LACUNAS - S. Hacon, S. Hacon; Barrocas, P. R. G.; de Vasconcellos, A. C. S.; Barcellos, C.; Wasserman, J. C.; Campos, R. C. (Geochimica Brasiliensis, 2012)